Pengaruh Pengalaman Auditor Terhadap Kualitas Audit (Studi Literatur) - Shalshabila Shafa; Kasmanto Miharja; Devi Savira (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
The auditor's experience aspect is a crucial factor in determining the quality of audit activities at KAP. The research is aimed at exploring the impact of aspects of an auditor's experience on the quality of audit activities and results based on relevant literature studies. The research method uses a narrative literature review to synthesize evidence from various literature sources. The results of the analysis show that the auditor's experience aspect has a close, positive and significant relationship to the auditor's ability to identify material errors and fraud in the form of client financial reports. The implication of this research is the importance of developing auditor experience as a strategy to improve audit standards and public trust.